Visualisasi Data Aset Tidak Bergerak Menggunakan Looker Studio Pada PT XYZ - Chepy Perdana; Usep Abdul Rosid; Bian Austin Okto (Jurnal Informatika, 2024)
PT XYZ is a company engaged in the electronics industry. This company has several divisions and units, one of which is the Project Deployment Center (PDC) division has a unit called Project Operation-Commercial Sector (POCS). The task of this unit is to meet the need for information and materials needed for project operations in accordance with the approved plan and to monitor and evaluate all commercial sector project activities. In carrying out project operations, especially related to monitoring, this unit only displays data in the form of google spreadsheets, so project managers and teams have difficulty in monitoring the data of their immovable assets. To solve this problem, it is necessary to visualize data in the form of a monitoring dashboard. This monitoring dashboard includes registration, borrowing, returns and calibration. Registration is required to register assets, borrowing and return transactions are intended if the assets are borrowed and returned, calibration is intended if the assets will be calibrated. This monitoring dashboard uses Looker Studio which functions as a data visualization medium in the form of a monitoring dashboard. The result of this work is to display a monitoring dashboard that has an attractive and informative appearance so that with the dashboard, it is hoped that it can help project managers and teams in monitoring asset data easily and quickly.